How do you factor #2y(y+60)=0#?

1 Answer
Aug 19, 2017

Answer:

This expression has already been factored, so you can go straight to the answers. There are two, because if you multiply the factors back together, the unknown has an exponent of two (#y^2#).

Explanation:

We have: #2y(y+60)=0#

So if you were to multiply either factor by the other, you would get #0#.

Here that means when #(y+60)# is multiplied by #2y# the result is #0#.

And when #2y=0to# then #y=0/2to# or #y=0to# Ans 1)

And when #(y+60)=0to# then #y+60=0to#

or #y=-60to# Ans 2)